Chronotypes and objectively measured physical activity and sedentary time at midlife - Nauha, L. (Laura); Jurvelin, H. (Heidi); Ala-Mursula, L. (Leena); Niemelä, M. (Maisa); Jämsä, T. (Timo); Kangas, M. (Maarit); Korpelainen, R. (Raija) (John Wiley & Sons, 2020)
Abstract Morning, day, or evening chronotypes differ by the circadian timing of alertness and the preferred timing of sleep. It has been suggested that evening chronotype is associated with low physical activity (PA) and high sedentary time (SED). Our aim was to investigate whether such an association is confirmed by objectively measured PA and SED. In 46‐year follow‐up of the Northern Finland Birth Cohort 1966 study, total PA (MET min/day) and SED (min/day) among 5156 participants were determined using wrist‐worn accelerometers for 14 days. We used the shortened Morningness‐Eveningness Questionnaire to define participants’ chronotypes. As covariates, we used self‐reported physical strenuousness of work, health, and demographics, and clinical measures. We used adjusted general linear models (B coefficients with 95% confidence intervals, CI) to analyze how chronotype was related to total PA or SED. As compared to evening chronotype, men with day and morning chronotypes had higher total PA volumes (adjusted B 75.2, 95% CI [8.1, 142.4], P = .028, and 98.6, [30.2, 167.1], P = .005). Men with day and morning chronotypes had less SED (−35.8, [−53.8, −17.8], P < .0001, and − 38.6, [−56.9, −20.2], P < .0001). Among women, morning chronotype was associated with higher total PA (57.8, [10.5, 105.0], P = .017), whereas no association between chronotype and SED emerged. Evening chronotype was associated with low objectively measured PA in both sexes and with high SED in men, even after adjustments for established potential confounders. Chronotype should be considered in PA promotion. Correction In the abstract, a typo (missing − -sign) was corrected in the sentence : Men with day and morning chronotypes had less SED (−35.8, [−53.8, −17.8], p < 0.0001, and −38.6, [−56.9, −20.2], p < 0.0001).